Development of energy-efficient ir dryer for plant raw materials - Черевко, Александр Иванович; Киптелая, Людмила Васильевна; Михайлов, Валерий Михайлович; Загорулько, Алексей Евгеньевич; Загорулько, Андрей Николаевич (Eastern-European Journal of Enterprise Technologies, 2015)
Due to the deterioration of the ecological situation in Ukraine and other European countries, the main purpose of the processing industry is the manufacture of high-quality dried products with a high content of biologically active substances (BAS). Since the existing technological equipment for processing plant raw materials has high efficiency and long heat treatment period, which leads to the product quality deterioration, the development of energy-efficient IR dryers is the topical issue. To implement these requirements it is necessary to solve the following tasks, namely to explore modern IR generators and justify the use of inertialess film electric heater (FEH), develop the IR dryer with an optimal shape of the working chamber, simulate the heat flow distribution on the receiving surface using TracePro software and develop energy-saving system and mechanism for shaking the wire-mesh trays based on the IR device. As a result of the research, a vertical cylindrical IR dryer ("VC-IR-20"), which has the energy- and resource-saving characteristics for manufacturing high-quality dried plant semi-finished products with a high content of biologically active substances (BAS), which can be used in most food productions, pharmacology, as impurities, and in bulk form, was developed. The device has an optimal geometric shape of the working chamber in the form of a vertical cylinder, ensuring maximum uniform heat flow distribution on the receiving surface. The developed device uses 100% of the secondary moist air to heat the fresh air by approximately 5°C, and the shaking mechanism prevents caking of plant raw materials during drying.